PERENCANAAN INFRASTRUKTUR JALAN DAN DRAINASE KAWASAN PERUMAHAN CLUSTER JATI PADANG, JAKARTA SELATAN - An An Anisarida; Febrian Febrian; Muhammad Rizky Pratama Janizar (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The development of residential areas in urban regions requires reliable basic infrastructure, particularly neighborhood roads and drainage systems. Poorly planned infrastructure can lead to waterlogging, deterioration of road quality, and reduced comfort and safety for residents. However, previous studies generally address drainage systems and pavement design separately, indicating that integrated infrastructure planning approaches remain limited. This study aims to develop an integrated infrastructure planning for the Jati Padang residential cluster in South Jakarta, including land grading, drainage system design, and pavement planning using paving blocks. The methods employed include hydrological analysis based on rainfall data from the BMKG Halim Perdana Kusuma Station (2009–2018), flood discharge estimation using the Rational Method and Synthetic Unit Hydrograph (HSS) ITB-1, and pavement design based on subgrade CBR values obtained from DCP testing. The novelty of this study lies in the integrated planning approach that combines land grading, hydrological and hydraulic analysis, and pavement design within a single framework based on actual field conditions. The results indicate that the 10-year return period rainfall is 160.67 mm, with a peak discharge of 0.205 m³/s. The designed u-ditch drainage channel (width 0.4 m; height 0.6 m) is capable of accommodating the design discharge, while the paving block pavement is designed based on a CBR value of 5.27%. This planning approach is expected to serve as a reference for developing safe, efficient, and sustainable residential infrastructure.